Pengaruh Kemudahan Penggunaan, Kemanfaatan, Literasi Keuangan, dan Gaya Hidup Hedonis Terhadap Perilaku Berutang Mahasiswa Pengguna Shopee Paylater - Junaidin; Anuggrah, Anggun (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The growth of digital financial services via the "Buy Now, Pay Later" (BNPL) model—such as Shopee PayLater—offers students easy access to financing but also risks fostering consumptive borrowing behavior. This study aims to analyze the impact of perceived ease of use, perceived usefulness, financial literacy, and hedonistic lifestyle on the borrowing behavior of Universitas Bima Internasional students who use Shopee PayLater. A quantitative approach with a causal-associative method was employed. Data were collected via questionnaires from 105 student users of Shopee PayLater, selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results indicate that perceived ease of use has a positive and significant effect on borrowing behavior (β = 0.214; p = 0.021), as does perceived usefulness (β = 0.263; p = 0.005) and hedonistic lifestyle (β = 0.319; p < 0.001); conversely, financial literacy has a negative and significant effect (β = -0.286; p = 0.002). An R² value of 0.650 demonstrates that these four variables explain 65.0% of the variation in students' borrowing behavior. These findings suggest that the convenience and utility of BNPL, along with a hedonistic lifestyle, can increase the propensity to borrow, whereas financial literacy plays a role in mitigating this tendency. The study underscores the importance of strengthening students' financial literacy to ensure that BNPL services are used wisely and responsibly